South-South learning on index insurance - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 20-22 January, 2014, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) hosted a workshop on Mobilizing a CGIAR Agricultural Insurance Research Community. The workshop took place at the International Food Policy Research Institute in Washington, DC. CCAFS Regional Program Leader Pramod Aggarwal spoke about the potential for South-South collaboration based on learning about India's index insurance experience. Read more about CCAFS work on index insurance: https://ccafs.cgiar.org/weather-index-based-insurance